Failure mindset is associated with achievement orientation among Singaporean children - Chan, Trena Yun Ting (Nanyang Technological University, 2023)
Past studies have suggested associations between children’s mindset and Achievement Orientation, yet most research was conducted with children from Western countries. This study aims to examine how Failure and Intelligence Mindset relate to children’s Achievement Orientation across culture. Online interviews were conducted with 124 Singaporean and 122 U.S. children aged between 4 to 9, during which Achievement Orientation was measured with a hypothetical scenario, and mindset was measured with child-friendly Likert scale items adapted from previous surveys. Within the Singaporean sample, 28 were Malay while the remaining were Chinese. Results showed that after controlling for age, the correlation between Intelligence Mindset and Achievement Orientation was not significant for either culture. Failure Mindset correlated with Achievement Orientation for Singaporean children but not for U.S. children. These findings suggest that Failure Mindset may be especially important in Asian culture, where a failure-is-motivating mindset can encourage children to face challenging tasks. Additionally, the results showed that unlike U.S. and Singaporean Chinese children, age is not significantly correlated to Achievement Orientation for Singaporean Malay children. Results also showed that household income influences Achievement Orientation within the Singaporean sample. These findings demonstrate nuances within the same cultural context which may be important to understand how to encourage mastery orientation for children.